Original Extension of a Human-Oriented Benefits Platform Using BI And AI For Human Resources Management - Marzenna MIŁEK; Tomasz PROTASOWICKI; Małgorzata ŻMIGRODZKA (Communications of International Proceedings, 2024)
The purpose of this article is to present a possibility a platform that is designed for effective human resource management using BI (Business Intelligence) and AI (Artificial Intelligence) human-centric solutions. In particular, this applies to the possibility of extending Carrotspot's existing benefit platform with a new functional scope using BI. In the literature we can find the examples of applications of artificial intelligence algorithms to the management of the organization however, they do not exhaust the topic presented in the article. The paper was prepared with the use of the critical literature review method mainly in the field of safety culture in aviation and how to manage this problem. The study was also conducted on the basis of the analysis of the capabilities of the Carrotspot's platform in the field of aviation. Its unique solutions provide a much larger field of development than the previously described research results presented in the available literature. In the article, the authors included the studied phenomenon in a special way taking into account the implementation of the project and an attempt to implement it in the aviation environment in the field of human resource management and the creation of a safety culture using the tools available on the platform. The conclusion synthesizes the presented approach and indicates the directions of further research in the considered area. The conclusion also shows how properly motivated personnel affect safety and customer satisfaction.
Keywords: BI; AI; software development; human resources management; safety culture in aviation